AN ANALYSIS OF STUDENTS' NEED IN ENGLISH LEARNING FOR THE STUDENTS OF STT MIGAS CILACAP - Windiarti, Sutri; Subekti Proklamanto, Aan (English Education Department, 2025)
Needs analysis plays a vital role in the development of English for Specific Purposes (ESP) program because it is through this learning needs analysis that information about students' wants, needs, and gaps in their English learning can be identified. This research aims to identify the English learning needs of STT Migas Cilacap Students. The majors are Petroleum Engineering, Occupational Safety and Health, and Oil and Gas Processing. A questionnaire was used as a data collection instrument, which was distributed to 45 students of STT Migas Cilacap. Besides, student interviews will also be done in this research to support the data results. The results of this learning needs analysis show that the main goal of students learning English is to support their self-development and communication with foreign speakers. Therefore, they place more emphasis on speaking skills. Although other language skills are also considered important to be developed, all of them must be in line with their professional career development. Then, they prefer to study by doing exercises in English learning. After that, their difficulties in English learning are in grammar and speaking fluently. They often to do exercise in writing and speaking so they can speak fluently with the correct grammar. It is hoped that the results of this learning needs analysis can be used as a guide in the development of English teaching materials for STT Migas Cilacap students.